Analisis Faktor-Faktor yang Mempengaruhi Persepsi Penggunaan Informasi Akuntansi pada Usaha Mikro Kecil dan Menengah - Feronica Try Octaviana Purba; Argo Putra Prima (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze the factors that influence the perception of the use of accounting information in Micro, Small and Medium Enterprises MSMEs in Batam City. This study used a descriptive and quantitative statistical approach with a population of 990 MSMEs registered at the Batam City Office of Cooperatives and Micro Enterprises with a sample of 100 respondents using a questionnaire as a data collection instrument. From the analysis of the data, the results show that accounting knowledge affects the perception of the use of accounting information with t count 2.377 > t table 1.984, business experience influences perceptions of the use of accounting information with t count 3.675 > t table 1.984, business scale does not affect the perception of the use of accounting information with t count 1.790 > t table 1.984. Simultaneously the results of the F test of accounting knowledge, business experience and business scale affect the perception of the use of accounting information with an F count 38.357 > F table 2.70.